Fear v Hope: The battle for language - C. Howe (Law Text Culture, 2008)
These poems have been written in response to the many articles focusing on the ‘War on Terror’ that have appeared in Australian newspapers over the past six years. I have been disturbed by the use of language in many of these articles, which have been produced by the mass media to be consumed by the reader, as opposed to pondered, interrogated, challenged and engaged with on a critical and creative level. The complexities and nuances of language use have been overlooked in the widespread acceptance of terms such as ‘war’, ‘terror’, ‘insurgent’, ‘freedom’, etc.